Depletion of PHD3 protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis. (March 2015) - Xie, Liang; Pi, Xinchun; Wang, Zhongjing; He, Jun; Willis, Monte S.; Patterson, Cam
Abstract: PHD3, a member of a family of Prolyl-4 Hydroxylase Domain (PHD) proteins, has long been considered a pro-apoptotic protein. Although the pro-apoptotic effect of PHD3 requires its prolyl hydroxylase activity, it may be independent of HIF-1α, the common substrate of PHDs. PHD3 is highly expressed in the heart, however, its role in cardiomyocyte apoptosis remains unclear. This study was undertaken to determine whether inhibition or depletion of PHD3 inhibits cardiomyocyte apoptosis and attenuates myocardial injury induced by ischemia–reperfusion (I/R). PHD3 knockout mice and littermate controls were subjected to left anterior descending (LAD) coronary artery ligation for 40 min followed by reperfusion. Histochemical analysis using Evan's Blue, triphenyl-tetrazolium chloride and TUNEL staining, demonstrated that myocardial injury and cardiomyocyte apoptosis induced I/R injury were significantly attenuated in PHD3 knockout mice. PHD3 knockout mice exhibited no changes in HIF-1α protein level, the expression of some HIF target genes or the myocardium capillary density at physiological condition. However, depletion of PHD3 further enhanced the induction of HIF-1α protein at hypoxic condition and increased expression of HIF-1α inhibited cardiomyocyte apoptosis induced by hypoxia. In addition, it has been demonstrated that PHD3 plays an important role in ATR/Chk1/p53 pathway. Consistently, a prolyl hydroxylase inhibitor or depletion of PHD3 significantly inhibits the activation of Chk1 and p53 in cardiomyocytes and the subsequent apoptosis induced by doxorubicin, hydrogen peroxide or hypoxia/reoxygenation. Taken together, these data suggest that depletion of PHD3 leads to increased stabilization of HIF-1α and inhibition of DNA damage response, both of which may contribute to the cardioprotective effect seen with depletion of PHD3. Highlights: Depletion of PHD3 attenuates myocardial injury induced by ischemia–reperfusion. Depletion of PHD3 further stabilizes HIF-1α at hypoxic condition. HIF-1α inhibits cardiomyocyte apoptosis induced by hypoxia. Depletion of PHD3 inhibits Chk1/p53 activation induced by oxidative stress. Depletion of PHD3 inhibits cardiomyocyte apoptosis induced by oxidative stress.